Classification trends with the ICPC-2 Z Chapter from 2006 to 2011 in a Family Medicine Health Centre in Coimbra, Portugal - Luiz Miguel Santiago; Paula Ricardo Miranda; Phililppe Botas (Sociedade Brasileira de Medicina de Família e Comunidade, 2013)
Objective: To study the classification trend in ICPC-2, Z Chapter, in the period 2006-2011, in terms of frequency in variation of the total number of sign and symptom components; volume of "population-adjusted classification"; and - based on SOAP for collecting information - which of its components were more frequently recorded in the Subjective (S) and Assessment (A) fields. Methods: Cross-sectional, observational, descriptive study of electronic registries in the SAM (Serviço de Apoio ao Médico - medical visit assistant software) using data collection tool (SAM-Statistics) in August 2012 in Coimbra, central Portugal. Classification volume was studied using codes/1000 inhab/day. The population for each year was calculated based on the middle of each study period. The six most frequent codes in each year were selected. Results: A positive increasing trend was found between 2006 and 2011 in the Subjective and Assessment recording fields, in terms of the total of codes (S:+4,83; A:+6,44) and classification volume - codes/1000 inhab/day (S:+4,40; A:+6,44), as well as in the percentage of different components of the Z sign and symptom codes (S: +0,30; A: +0,56). Conclusions: From 2006 to 2011, a positive trend was found in the ICPC-2 Z Chapter classification, which was more important in Assessment (A), and the type of components recorded through the SOAP method. Hence, continuing medical education is still necessary to improve performance in the crucial task of classification, registering and clinical noting to avoid lack of clinical information.